The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12879-017-2675-3
|View full text |Cite
|
Sign up to set email alerts
|

Incident Mycobacterium tuberculosis infection in household contacts of infectious tuberculosis patients in Brazil

Abstract: BackgroundIn household contact investigations of tuberculosis (TB), a second tuberculin skin test (TST) obtained several weeks after a first negative result consistently identifies individuals that undergo TST conversion. It remains unclear whether this delay in M. tuberculosis infection is related to differences in the infectious exposure, TST boosting, partial host resistance, or some other factor.MethodsWe conducted a household contact study Vitória, Brazil. Between 2008 and 2013, we identified culture-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
(48 reference statements)
1
14
0
2
Order By: Relevance
“…These results were then used to estimate the range of possible mutation rates and generation times of M. tuberculosis during LTBI. In a previously described HHC study performed in Vitória, Brazil between February 2008 and October 2013 22 , we had identified 160 households that fit the case definition of containing a highly infectious case of acid-fast bacilli (AFB) smear-positive pulmonary TB, had at least three HHCs, and did not fulfill any exclusion criteria. Between the beginning of the HHC study in 2008 and the end of the study in 2015, 72 HHCs associated with 62 of these ICs were found to have developed active TB ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were then used to estimate the range of possible mutation rates and generation times of M. tuberculosis during LTBI. In a previously described HHC study performed in Vitória, Brazil between February 2008 and October 2013 22 , we had identified 160 households that fit the case definition of containing a highly infectious case of acid-fast bacilli (AFB) smear-positive pulmonary TB, had at least three HHCs, and did not fulfill any exclusion criteria. Between the beginning of the HHC study in 2008 and the end of the study in 2015, 72 HHCs associated with 62 of these ICs were found to have developed active TB ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We obtained M. tuberculosis cultures from participants enrolled in a HHC study performed at the Núcleo do Doenças Infecciosas (NDI) located in Vitória, the capital city of the State of Espírito Santo, Brazil. Participant enrollment and sample collection has been described 22 . In brief, the NDI has organized a network of 16 TB clinics in the metropolitan region of Vitória 28 , which facilitated the identification of index TB cases as well as secondary TB cases in HHCs after initial ascertainment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in Table 1 , studies with at least two years of longitudinal observation of HC conversion of TST demonstrated a frequency of early clearance ranging from 3.4% 14 to 26.8%, both in Uganda 15 . Whereas the TB Network study that followed HC conversion of IGRA demonstrated that about 58% of exposed HCs lacked evidence of immune sensitization, other studies had a less rigorous definition, as they varied by time of follow-up with individual as well as the likelihood of exposure to TB 16 20 . Presumably, in some of these studies, higher rates of TST- and IGRA-negative HCs could be explained by diminished exposure to Mtb.…”
Section: Evidence For Early Clearancementioning
confidence: 99%
“…Using binomial risk models (9) and data from (2), we evaluated two plausible mechanisms by which reinfection during this early, critical period can account for the increased disease risk: an independent effect of each infection on risk of progression (reinfection model) and a high risk of progression once the cumulative number of exposures exceeds a threshold value (threshold model). Contacts of TB cases producing aerosols with high burdens of Mycobacterium tuberculosis are more likely to become cases (10)(11)(12), suggesting an inoculum effect as a plausible biological mechanism for both these models. Both models are consistent with the observed data, though neither fully accounts for the observed high risk of active disease in this population following an initial exposure.…”
Section: Introductionmentioning
confidence: 99%